Partição de assimilados e produção de matéria seca do feijão (Phaseolus vulgaris L.) em dois sistemas de associação com o milho - Cardoso, Milton José; Nogueira Fontes, Luiz Antônio; Fernandes Lopes, Nei; Domingos Galvão, José (Revista Ceres, 2025)
Growth,morphology, dry matter partition and total dry matter accumulation were studied in Phaseolus vulgaris L. cv. Negrito 897, grown in association with maize. The systems of association consisted of beans grown between rows or within rows of corn which had hills spaced at 0.25, 0.5 or 1.0m with one, two and four plants per meter of row, respectively.